Foreign acts of state and the conflict of laws - Dickinson, A (Sweet and Maxwell, 2022)
In 'Maduro Board of the Central Bank of Venezuela v Guiado Board of the Central Bank of Venezuela' [2021] UKSC 57; [2022] 2 W.L.R. 167, the Supreme Court took the opportunity to clarify certain aspects of the law concerning the treatment of foreign acts of state, while leaving for future determination other critical aspects of the dispute between rival factions in the ongoing struggle for political and economic control in Venezuela.